(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Short-term plans for open pit mining were given along with short-term plans for the border area of the mine. This model simulates a complex system of trucks and shovels and takes into account the uncertainties associated with the operation of trucks and shovels. This ensures that operational plans are aligned with net present value and ensures that the planning phase is more thorough. Two main subproblems are addressed in this study. First of all, there is the problem of choosing equipment that determines the number of trucks and shovels. In the second subproblem, key performance indicators are evaluated using resources defined in the front loader and shovel system. In both stages, the optimal short-run production schedule is a key factor in the model. The proposed simulation model is developed using simulation software and is applied to a real open pit iron ore mine. As an example, several research processes on the planning of the location of mining enterprises are given. Operation of open-pit mining enterprises is usually carried out through the work plan (technical documents) of the mining stages. In opencast metal ore mining, each push operates one or more drilling rigs in the mining process, and the main operational tasks include: Drilling and blasting, loading and hauling are the main processes in opencast mines. In large open pits, shovels and front loaders can be used to perform loading operations. During the planning process, the type and number of loaders are selected and their performance is determined. Connie’s gravity and mining speed indicate productivity. This determines its shape and size, which is a relevant step in the design of open pits, and the description of the location and sequence of loading equipment depends on the final process of each pusher. The arrangement of loading equipment in the mine is usually called the formation scheme of the exploitation period. This term is widely used in the mining industry. The purpose of this paper is to introduce strategic mine planning activities in the context of the mining scheme concept in open pit mining. The first part introduces the concept and shows examples where the drawing size is set and the number of spades is changed. Technical processes that may be considered by an open pit planner are outlined.